Brain Size and Life History Interact to Predict Urban Tolerance in Birds - Sayol, Ferran; Sol, Daniel; Pigot, Alex L. (Frontiers in Ecology and Evolution, 2020)
Urbanization is a major driver of local biodiversity losses, but the traits that determine whether species are able to tolerate urban environments remain poorly understood. Theory suggests that a larger brain should provide higher tolerance to urbanization by enhancing behavioral flexibility to cope with novel challenges. However, assembling empirical evidence for a link between brain size and tolerance to urbanization has proven to be difficult, perhaps because the effect of the brain interacts with life history to influence persistence in urban environments. Here, we provide a global-scale assessment of the role of brain size on urban tolerance, combining quantitative estimations of urban tolerance with detailed information on brain size, life history and ecology for 629 avian species across 27 cities. Our analysis confirms the expected positive association between brain size and urban tolerance, but shows that the relationship is more complex than previously shown. While a large relative brain size generally increases urban tolerance, species with small brains can still attain high success in urban environments if they spread the risk of reproduction in multiple events (i.e. have a low brood value). These alternative strategies, although uncommon in natural conditions, seem to be favored in urban environments, fundamentally restructuring the composition of urban communities. Thus, our results support the notion that brain size mediates tolerance to urbanization, but also shows that there are alternative ways of exploiting urban environments. Our findings reconcile previous conflicting results regarding the effect of brain size on urban tolerance, and provide the basis for improved predictions of the responses of organisms to increasing urbanization over the coming decades.